Rules and regulations of The United Brothers' Birmingham Benefit Society (London : J.S. Forsaith & Son, Printers (T.U.), 1908)
1908 1908 1900s 18 pages INDEX RULE Admission of New Members 1 Alteration of Rules 26 Amount of Contribution 1 Annual General Meeting 28 Appointment of Auditors 25 „ „ Secretary 4 „ „ Stewards 5 „ „ Trustees 18 Arbitration 22 Assistance to Members in Distress 29 Clearing the Books on the last Quarterly Night ...... 24 Dissolution of the Society 23 Division of the Surplus of Sick Fund......... 27 Duty of President 15 Duties of Visitors 6 Election of Committee 28 Free Member's Death or Wife's Death 17 Members Declaring On the Funds 6 „ „ Off „ 7 „ Imposing on the Funds 11 „ Guilty of Embezzlement, &c 20 Notice of Meetings 19 Payment of Sick Pay 8 Permission to Sick Members to go into the Country 9 Power of Stewards to raise Contributions 21 Proposing Members 2 Receiving Injury by Fighting 10 Security from Treasurer 16 Sick Members Absent from Home 12 Stewards Declaring on the Funds 13 Suspension from Benefits 14 Trades, &c. 3 345/7/2/2